Anatomical analysis of different helical plate designs for proximal humeral shaft fracture fixation. (1st June 2022) - Pastor, T; Kastner, P; Souleiman, F; Gehweiler, D; Miglorini, F; Link, B-C; Beeres, F J P; Babst, R; Nebelung, S; Ganse, B; Schoeneberg, C; Gueorguiev, B; et al.
Abstract: Objective: Helical plates are preferably used for proximal humeral shaft fracture fixation with metaphyseal extension into the humeral head and potentially avoid radial nerve irritation as compared to straight plates. The aims of this study were: (1) to investigate the safety of applying different long plate designs (straight, 45°-, 90°-helical and ALPS) in MIPO-technique to the humerus and (2) to assess and compare their distances to adjacent anatomical structures at risk. Methods: MIPO was performed in 16 human cadaveric humeri using either a straight plate (group1), a 45°-helical (group2), a 90°-helical (group3) or an ALPS (group4). Using CT-angiography, distances between brachial arteries and plates were evaluated. Following, all specimens were dissected, and distances to the axillary, radial and musculocutaneous nerve were evaluated. Results: None of the specimens demonstrated injuries of the anatomical structures at risk after MIPO with all investigated plate designs. Closest overall distance (mm(range)) between each plate and the radial nerve was 1(1–3) in group1, 7(2–11) in group2, 14(7–25) in group3 and 6(3–8) in group4. It was significantly longer in group3 and significantly shorter in group1 as compared to all other groups, p<0.001. Closest overall distance (mm(range)) between each plate and the musculocutaneous nerve was 16(8–28) in group1, 11(7–18) in group2, 3(2–4) in group3 and 6(3–8) in group4. It was significantly longer in group1 and significantly shorter in group3 as compared to all other groups, p<0.001. Closest overall distance (mm(range)) between each plate and the brachial artery was 21(18–23) in group1, 7(6–7) in group2, 4(3–5) in group3 and 7(6–7) in group4. It was significantly longer in group1 and significantly shorter in group3 as compared to all other groups, p<0.021. Conclusion: MIPO with 45°- and 90°-helical plates as well as ALPS is safely feasible and showed a significant greater distance to the radial nerve compared to straight plates. However, distances remain low, and attention must be paid to the musculocutaneous nerve and the brachial artery when MIPO is used with ALPS, 45°- and 90°-helical implants. Moreover, the anterior part of the deltoid insertion will be detached when using 90°-helical and ALPS implants in MIPO-technique.